Pemanfaatan Pangan Lokal sebagai Upaya Pencegahan Balita Stunting di Desa Ciaruteun Udik: Utilization of Local Food as an Effort to Prevent Stunting Toddlers in Ciaruteun Udik Village - Tika Noor Prastia; Rahma Listyandini; Hurip Nuryana; Malda Afrianti Setiadi; Rapika Dea Sintani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
The prevalence of stunting increased during the pandemic in the work area of ​​the Cibungbulang Health Center, Bogor Regency. Stunting must be prevented from the first 1000 days of life, one of which is by providing adequate supplementary food (PMT). This community empowerment activity aims to increase the use of nutritious local food ingredients in processed PMT menus. The activity has been carried out during June to August 2021. The program targets are posyandu cadres in Ciaruteun Udik Village, Cibungbubulang, Bogor Regency. The activity consists of three stages: preparation, intervention, and evaluation. The intervention carried out was providing counseling materials through access to WhatsApp Group and videos uploaded to YouTube. The program ended with a local food-based PMT menu creation competition. The results of the intervention showed that there was an increase in the knowledge of cadres after receiving counseling. At least 75% of cadres can correctly answer all post-test questions. The competition results showed that the cadres could practice the processed PMT menu with local food ingredients. It can be concluded that the level of knowledge of posyandu cadres in Ciaruteun Udik Village has increased chiefly. There is a need for follow-up activities to improve the skills of cadres and mothers of toddlers in processing PMT menus with food that can be given during posyandu activities or processed by mothers of toddlers themselves as snacks for children at home.